Strategic fouling and sport as play. Issue 1 (2nd January 2017) - Russell, J. S.
Abstract: This essay argues that defences of strategic fouling in sport are enriched and supported by better recognizing the role of play in sport. A common characteristic of play is its disengagement from the everyday, in particular its moral disengagement. If sport in its best manifestations is a species of play, then we should expect to find some moral disengagement there. And indeed we do in a variety of ways. Strategic fouling affords a useful example to illustrate and support this claim and to examine the limits of that sort of disengagement. It is argued that while strategic fouling is morally problematic, it can be a sort of playful 'competitive shenanigan' that should be tolerated at times for the way it adds to the challenge and drama of sport. This allows us to better recognize the complexity and depth of sport and the way it reflects fundamental human values. Like everyday life, sport challenges us to weigh morality, perfection, and play against each other in ways that give each sphere of value its due and that contribute to rewarding and meaningful activities and lives.